Single-cell RNA sequencing reveals distinct tumor microenvironment of ground glass nodules and solid nodules in lung adenocarcinoma - Huang, Xiaofeng; Lu, Zhimeng; Jiang, Xuewei; Zhang, Zhe; Yan, Kun; Yu, Guiping (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Lung adenocarcinoma (LUAD) is the most prevalent lung cancer. LUAD presents as ground glass nodules (GGN) and solid nodules (SN) in imaging studies. GGN is an early type of LUAD with good prognosis. However, SN exhibits a more malignant behavior than GGN, including worse pathological staging and tumor prognosis. The mechanism leading to the different malignancy levels of GGN and SN remains elusive. Methods: Three patients with GGN and three patients with SN diagnosed with early LUAD were enrolled. The tumor samples were digested to a single-cell suspension and analyzed using 10× Genomic Single-cell ribonucleic acid sequences (scRNA-seq) techniques. Results: A total of 15,902 cells were obtained and classified into nine major types. The tumor microenvironment (TME) was subsequently described in detail. ScRNA-seq revealed that ribosome-related pathways and cell adhesion played similar but distinct roles in the two groups. SN also had more active cell proliferation, enriched cell cycle regulatory pathways, and severe inflammatory responses. Conclusion: We observed changes in the cellular composition and transcriptomic profile of GGN and SN. The study improved the understanding of the underlying mechanisms of lung carcinogenesis and contributed to lung cancer prevention and treatment.